Computational Fluid Dynamics Simulation of the Upper Airway of Obstructive Sleep Apnea Syndrome by Muller Maneuver - 聂萍 徐晓珑 唐艳梅 王晓玲 薛晓晨 吴亚东 朱敏 (Journal of Huazhong University of Science and Technology. Medical sciences, 2015)
This study aimed to use computer simulation to describe the fluid dynamic characteristics in patients with obstructive sleep apnea syndrome（OSAS） and to evaluate the difference between during quiet respiration and the Muller maneuver（MM）. Seven patients with OSAS were involved to perform computed tomographic（CT） scanning during quiet respiration and the MM. CT data in DICOM format were transformed into an anatomically three-dimensional computational fluid dynamics（CFD） model of the upper airway. The velocity magnitude, relative pressure, and flow distribution were obtained. Numerical simulation of airflow was performed to discuss how the MM affected airflow in the upper airway. To measure the discrepancy, the SPSS19.0 software package was utilized for statistic analysis. The results showed that the shape of the upper airway became narrower, and the pressure decreased during the MM. The minimal cross-sectional area（MCSA） of velopharynx was significantly decreased（P〈0.05） and the airflow velocity in MCSAs of velopharynx and glossopharynx significantly accelerated（P〈0.05） during the MM. This study demonstrated the possibility of CFD model combined with the MM for understanding pharyngeal aerodynamics in the pathophysiology of OSAS.